PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI BANGUN DATAR BERBANTUAN MEDIA POP UP BOOK DI SD - Mawaddah, Mawaddah; Yantoro; Violita Zahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Project Based Learning (PjBL) model in improving students’ critical thinking skills on the topic of plane figures assisted by pop-up book media in elementary school. The research subjects were fifth-grade students of SDN 127/1 Petajen. The method employed was Classroom Action Research (CAR) with both qualitative and quantitative approaches. Data validity was tested using source and technique triangulation. The research was considered successful if at least 70% of students achieved a good level of critical thinking skills. The results showed that in the first cycle, learning mastery reached 60%, while in the second cycle it increased to 86.67%. This achievement exceeded the predetermined success criteria. Thus, the implementation of the PjBL model assisted by pop-up book media proved effective in improving the critical thinking skills of fifth-grade students.